Web Scraping On Forecast Report Form Of Geomagnet - Setyanto Cahyo Pranoto (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
The increasing information encourages the development of new technologies so that data and information processing can be done easily and quickly. One of them in terms of obtaining information obtained from the website and most of the current studies targeting this task are mostly about automated web data extraction. Web scraping is a process of extracting valuable and interesting text information from web pages. To realize space weather prediction information services, including geomagnetic activity, Forecast Report Form of geomagnetic (FRF) application was developed using the web scraping method. The results obtained indicate that web scraping reliable for collecting large amounts of data more quickly automatically, efficient and can present expected result. Black box testing is used to test the web scrapping process.